Social work and public health: challenges in the work of the social worker in the care of primary health care users (Research, Society and Development, 2020)
The study aimed to identify the challenges encountered by the Social Worker in the field of primary health care, through scientific productions made available in online journals, from the year 2010 to 2019. This is an integrative literature review, carried out in databases of the Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO) and PubMed. Data were collected in October and November 2020. For this purpose, the Health Sciences Descriptors (DeCS) were used, namely: “Social Assistants”, “Primary Health Care” and “Social Service”. The total sample of the study consisted of 26 previously selected articles, and after full analysis and exclusion criteria, it resulted in a final sample of 5 articles. From the selected publications, two thematic categories emerged based on the focus of the studies: Social Work in Primary Care: trajectory and processes involved in its implementation; Social workers in Primary Care: contribution and challenges of these professionals in health. The study made it possible to show that the insertion of the Social Worker in primary health care is a relevant benchmark for Public Health. However, it is believed that this topic deserves greater attention on the part of the researchers in order to improve the theoretical and practical knowledge for the consolidation and recognition of the Social Service professional before Primary Care and the other professionals of the team.